(Re)positioning site dance : local acts, global perspectives - Barbour, Karen Nicole; Hunter, Victoria (Senior lecturer in dance); Kloetzel, Melanie (Intellect, 2019)
This co-authored book aims to articulate international approaches to making, performing and theorizing site-based dance. Intended for artists, scholars, and students, the approaches discussed are informed by interdisciplinary engagements with socio-cultural, political, economic and ecological perspectives.